2020
DOI: 10.3390/cancers12123597
|View full text |Cite
|
Sign up to set email alerts
|

Abemaciclib, A Selective CDK4/6 Inhibitor, Restricts the Growth of Pediatric Ependymomas

Abstract: Pediatric ependymomas are a type of malignant brain tumor that occurs in children. The overall 10-year survival rate has been reported as being 45–75%. Maximal safe surgical resection combined with adjuvant chemoradiation therapy is associated with the highest overall and progression-free survival rates. Despite aggressive treatment, one-third of ependymomas exhibit recurrence within 2 years of initial treatment. Therefore, this study aimed to find new agents to overcome chemoresistance and defer radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…It has been observed that abemaciclib induced cell death by inducing cytoplasmic vacuoles in cancer cells, and massive vacuolization led to atypical cell death, called methuosis ( Huang et al, 2018 ; Hino et al, 2020 ; Liang et al, 2020 ). Here, we found that abemaciclib treatment caused a striking accumulation of cytoplasmic vacuoles in A549 and H1650 cells, when compared with untreated cells ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that abemaciclib induced cell death by inducing cytoplasmic vacuoles in cancer cells, and massive vacuolization led to atypical cell death, called methuosis ( Huang et al, 2018 ; Hino et al, 2020 ; Liang et al, 2020 ). Here, we found that abemaciclib treatment caused a striking accumulation of cytoplasmic vacuoles in A549 and H1650 cells, when compared with untreated cells ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies have shown that abemaciclib inhibits the growth of ependymoma and glioblastoma in xenograft tumor models [10][11]. Moreover, a phase I clinical trial of abemaciclib showed that its concentration in cerebrospinal uid was similar to that in plasma [12].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that CDK4/6 inhibitors are potential drugs to treat brain tumors. Recent studies have demonstrated that CDK4/6 inhibitors effectively reduced cell proliferation and tumor growth in several brain tumors, including GBMs [ 8 , 9 , 10 , 11 ], AT/RTs [ 12 ], medulloblastomas [ 13 , 14 ] and ependymomas [ 15 ]. Although treatment with CDK4/6 inhibitors alone can delay tumor growth, some evidence demonstrated that CDK4/6 inhibitors induce nongenetic changes resulting in therapeutic failure, such as activation of the PI3K–AKT–mTOR signaling pathway, activation of cyclin E-CDK2 pathway and occurrence of autophagy [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%